2018
DOI: 10.1038/s41598-018-34690-3
|View full text |Cite
|
Sign up to set email alerts
|

Activity of frontal pole cortex reflecting hedonic tone of food and drink: fNIRS study in humans

Abstract: Cognitive and hedonic aspects of taste have been studied using different neuroimaging techniques in humans. However, the methods used are unsuitable for easy monitoring of hedonics induced by intake of foods and beverages. Here we have tried to monitor changes in oxygenated hemoglobin (oxyHb) levels in the anterior prefrontal cortex (aPFC, frontopolar cortex, Brodmann area 10) in response to intake of hedonically different edibles in healthy adults. When subjects tasted sweet and bitter solutions freely withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…For this purpose, various physiological reactions evoked by taste stimuli depending on the quality and/or hedonic tone have been more or less used for the objective evaluation of food and beverage hedonics (e.g., positive vs. negative; palatable vs. aversive; pleasant vs. unpleasant; acceptable vs. rejective). For example, taste effects can be observed in autonomic nerve activity such as salivary secretion [5,6], heart rate [7,8], and facial blood flow [9,10], hormonal changes such as insulin [11] and cortisol secretion [12], motor reactions such as facial expressions [13][14][15][16][17] and bodily reactivity [17], and brain activity [18][19][20][21]. A recent study from our lab revealed that pleasant and unpleasant edibles tended to elicit decreased and increased oxyhemoglobin (oxyHb) levels, respectively, within the ventral part of the anterior prefrontal cortex, suggesting that monitoring of oxyHb in this region may prove useful for the objective evaluation of food and beverage hedonics [21].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, various physiological reactions evoked by taste stimuli depending on the quality and/or hedonic tone have been more or less used for the objective evaluation of food and beverage hedonics (e.g., positive vs. negative; palatable vs. aversive; pleasant vs. unpleasant; acceptable vs. rejective). For example, taste effects can be observed in autonomic nerve activity such as salivary secretion [5,6], heart rate [7,8], and facial blood flow [9,10], hormonal changes such as insulin [11] and cortisol secretion [12], motor reactions such as facial expressions [13][14][15][16][17] and bodily reactivity [17], and brain activity [18][19][20][21]. A recent study from our lab revealed that pleasant and unpleasant edibles tended to elicit decreased and increased oxyhemoglobin (oxyHb) levels, respectively, within the ventral part of the anterior prefrontal cortex, suggesting that monitoring of oxyHb in this region may prove useful for the objective evaluation of food and beverage hedonics [21].…”
Section: Introductionmentioning
confidence: 99%
“…A bitter or sweet taste was previously shown to interact with corticomotor excitability [ 13 ] and brain oxygenation [ 16 ]. Although, recent results from our laboratory show no difference in brain oxygenation during repeated high-intensity cycling bouts with carbohydrate ingestion (including maple products) or water [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there is a lack of studies that have actually applied the methodology to research questions in food-and nutrition-related consumer behavior processes. Therefore, the potential of fNIRS for foodrelated contexts is yet not well-known (Minematsu, Ueji, & Yamamoto, 2018). Similarly, it is not yet clear in which areas of consumer research for food marketing fNIRS can be used best and what applications might be promising and what some limitations are concerning the application of fNIRS.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…as secondary cortical taste zone (Kringelbach, O'Doherty, Rolls, & Andrews, 2003;Rolls, 2015;Small et al, 2007;Small, 2012). Minematsu, Ueji, and Yamamoto (2018) showed that activity changes within different areas of the prefrontal cortex (PFC) can be an effective method to objectively evaluate the pleasantness of food and drinks in addition to subjective evaluation with sensory tests. The authors reported tendencies that pleasant tastes decrease oxygenated hemoglobin (oxyHb) in the PFC, while unpleasant tastes might increase them (Minematsu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation